The politics of fame - Burns, Eric (New Brunswick, New Jersey : Rutgers University Press, 2019)
"The Politics of Fame looks back on shifting trends in the culture and shifting currents in the human psyche that have compelled so many Americans to kneel before the thrones of so many strangers in so many different ways for so many years past and so very many to come"--
Life, liberty and the pursuit of fame -- The celebrity with a cause -- The cultural commodity -- At long last, class -- Circulation wars -- The press and the immigrants -- The deviancy of adulation -- The decreasing literacy rate -- The leveling forces of democracy -- The declining importance of faith -- The acceleration of haste -- The false intimacy of the media.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: United States -- Civilization; United States -- Social life and customs; Popular culture -- United States; Fame -- Social aspects -- United States; Celebrities -- United States -- Biography; États-Unis -- Civilisation; États-Unis -- Mœurs et coutumes; Culture populaire -- États-Unis.; Business Aspects; PERFORMING ARTS; Popular Culture; Media Studies; Celebrities; Civilization; Fame -- Social aspects; Manners and customs; Popular culture; United States; Electronic books; Biographies